Association between the disease severity and extraneural pressure induced by maximum elbow flexion in patients with cubital tunnel syndrome. Issue 3 (June 2013) - Ochi, Kensuke; Horiuchi, Yukio; Morisue, Hikaru; Harato, Kengo; Tanikawa, Hidenori; Okubo, Masashi
Abstract Extraneural pressure in the cubital tunnel is considered to be a major pathophysiological factor for cubital tunnel syndrome. Thus, it has been hypothesised that the higher extraneural pressure in the cubital tunnel should result in a more severe stage of cubital tunnel syndrome. Extraneural pressures in cubital tunnel at elbow maximum flexion of 41 patients with cubital tunnel syndrome were evaluated, and compared with their preoperative disease severity using McGowan's classification and Dellon's staging. Mean extraneural pressure was significantly higher in maximum elbow flexion than in maximum elbow extension (p < 0.001). However, no significant relation was seen between the severity of cubital tunnel syndrome and the extraneural pressure induced by maximum elbow flexion (McGowan's classification: p = 0.62; Dellon's staging: p = 0.92). The results suggested that the progression of disease severity of cubital tunnel syndrome may not be explained simply by dynamic pressure in the cubital tunnel, and other causative factors should also be contributing to the progression.